Siloxane based Organic-Inorganic Hybrid Polymers and their Applications for Nanostructured Optical/Photonic Components - Hidayat, Rahmat; Gomulya, Widiyanta; Pitriana, Pina; Irmansyah, Ryan; Miranti, Rany; Herman, Herman; Hidayat, Sahrul; Fitrilawati, Fitrilawati; Fujii, Akihiko; Ozaki, Masanori (Journal of Engineering and Technological Sciences, 2012)
We have studied the preparation of organic-inorganic hybrid polymer precursors  by  sol-gel  technique  and  their  utilization  for  nanostructured  optical components for photonic applications. The gel polymer precursors were prepared from  siloxane  modified  by  polymerizable  acrylate  groups,  which  can  be processed  further  by  photopolymerization  process.  Molecular  structure characterizations by means of the FTIR measurements indicate the conversion of C=C  bonds  into  C-C  bonds  after  photopolymerization.  This  bond  co nversion produces  high  cross-linking  between  the  organic  and  inorganic  moieties, resulting  in  thermally  stable and chemically resistant thin polymer layer which provide  unique  advantages  of  this  material  for  particular  optical/photonic applications.  By  employing  laser  interference  technique,  gratings  with periodicity between 400-1000 nm have been successfully fabricated. Application of  those  sub-micron  periodicity  of  grating  structure  as  active  elements  in optically  pumped  polymer  laser  system  and  Surface Plasmon Resonance  (SPR) based  measurement  system  have  been  also  explored.  The  experimental  results therefore  also  show  the  potential  applications  of  this  hybrid  polymer  as  a building material for micro/nano-photonics components.